KERAJAAN SIAK PADA MASA KEPEMIMPINAN SULTAN ASSAIDIS SYARIF HASYIM ABDUL JALIL SAIFUDDIN 1889-1908 - Muhammad Nur; Isjoni '; Kamaruddin ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Monarchy Siak is royal one get Malay pattern that is at beach east coast Sumatra. This monarchy is found on year 1723 at Buantan with founder and at a swoop first sultan is Reigning kecik who constitutes putera of Mahmud's Sultan Syah II. and Cik Pung's mother. Along forming this monarchy available twelve sultan that captain, in this scientific opus works through about Sultan Hasyim, 11th sultan. To the effect this research is (1 ) to know Siak's monarchies on governance term before Sultan Assaidis Syarif Hasyim Abdul Jalil Saifuddin (2 ) to know Sultan leadership terms Assaidis Syarif Hasyim Abdul Jalil Saifuddin at royal Siak (3 ) to know a stop to Sultan leadership terms Assaidis Syarif Hasyim Abdul Jalil Saifuddin. This research mengunakan methodics history. Result of this research is Assaidis Syarif Hasyim Abdul Jalil's Sultan constitute Sultan that takes in kejayaan to Siak Terkhusunya's monarchy on economics area. There are many thing which done by beliau on term captains Siak's monarchy there is umpteen beliau's opus on term captains Siak's monarchy which is Asserayah Hasyimiah's Palace development, Cream market building and prints Babul Qawaid's book (door all pegengan). besides sultan also interlace commerce relationship with peopled Chinese, Dutch and England those are on Singapore. Beliau also constitute Sultan that really at loves by its people because goodness and its wisdom in captain Siak's monarchy. meiliki's sultan some wife and child which is Juggernaut me Syarifah is gifted a child which is Juggernaut me Sulung (Sayid is Castrate), Embung's juggernaut, Encik Atik and Encik Rafeah is gifted a yaituTengku Long's child Turns White (Sayid is Muhammad).Key word: History, Monarchy.